Public policy : art and craft of policy analysis - Sapru, R. K. (New Delhi : PHI Learning, 2011)
The text book, now in its second edition, continues to provide an in-depth study of the various approaches for policy formulation, implementation and evaluation. It addresses issues in policy analysis, and explains the forces that influence the functioning of executive, legislature, judiciary, civil society and the administration. The book excellently reviews and evaluates the public policy literature, and exemplifies the author's long teaching and research experience in Punjab university.
Includes bibliographical references and index.
Keywords: Public policy; Policy Science; Public Administration